ECONOMIC STATUS OF THE BUKHARA EMIRATE IN THE LATE 19TH AND EARLY 20TH CENTURIES - Kh?likova R.E (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The article the government of tsarist Russia and its officials in Turkestan gradually entered the economy of the Bukhara Emirate and gained full control over it. According to archival sources, the tsarist authorities in the Samarkand region achieved hegemony in the issue of water distribution in Zarafshan, made Bukhara region dependent on water supply, subjugated the emirate's economy and made the emirate economically dependent. The Russian government pays great attention to the policy of occupying the internal markets of Russia and establishing its dominance in them. By the 70s and 90s of the 19th century, almost all industrial products necessary for the economic life of the emirate in the internal markets of Bukhara were imported from Russia. Tsarist Russia managed to further strengthen the policy of economic dependence of the Bukhara Emirate in the late 19th - early 20th centuries. The Russian government began to look for new opportunities for the full dependence of the Bukhara economy on it and began to realize them. Most importantly, the Russian bourgeoisie, which was directly interested in this policy, began to make new demands on the Russian government. As a result, the construction of railways and the formation of a flotilla in Central Asia, including in the Bukhara region, were achieved.